Penguatan Kapasitas LPD Desa Adat Di Bali Melalui Penyuratan Awig-Awig - Suwitra, I Made; Selamet, I Ketut; Datrini, Luh Kade (UI Scholars Hub, 2020)
The Village Credit Institution (LPD) owned by Desa Adat in Bali is oriented to strengthen the economy of indigenous peoples (krama adat) through lending (loans) and savings. The main source of capital for LPDs is the commitment and trust of all village manners which are submitted through the Adat Village Management Board (Prajuru) and the LPD Board. The strengthening of LPDs is in its management and accounting system and its supervision, because it is not uncommon for LPDs that are already large due to weak monitoring systems, poor management and accounting systems to misuse LPD funds utilization which causes LPD to no longer be operational or temporarily bankrupt like LPD in Adat Selulung Village, Kintamani Bangli. The bankruptcy of the LPD was also caused by the weakness of the Prajuru Adat in taking quick steps to replace corrupt officials on the one hand, while on the other hand it did not abolish its obligation to return funds that could not be accounted for through the imposition of civil sanctions or those known as pamidanda (sanction) in awig-awig.